Study of Common Fixed Point Theorems for Interpolative Contraction in Metric Space - Tiwari, Surendra Kumar; Ganvir, Jayant Prakash (Nepal Journal of Mathematical Sciences, 2024)
This paper aims to establish common fixed point results that can be addressed using an interpolative contraction condition proposed by Karapinar et al. [6] and Karapinar et al. [7] within a complete metric space. We have developed both the H-R type contraction and R-R-C–Rus–type contraction in the context of metric spaces, and we have proved related interpolation common fixed point theorem. Furthermore, we provide examples to illustrate the significance of our findings.